Redupnya Peran Politik Islam Di Masa Demokrasi Terpimpin (Studi Kasus Pembubaran Masyumi Oleh Presiden Soekarno) - Bathoro, Alim (Kemudi, 2018)
In the relationship between Islam and the state it is necessary to clarify the political decision of the ruler over the political role of Islam. As the majority religion in Indonesia, it is only natural that Islam becomes part of the relations in the political decision of the ruler. Therefore, examining the relationship between Islam and the state has an important meaning, for this reason the research seeks to explain the common thread of the state and Islam, especially how the political bargaining of Muslims with the authorities. In the period of Guided Democracy, President Soekarno was a political ruler, along with other political forces such as the Indonesian Army and the PKI. For this reason, tracking President Soekarnos past role in Guided Democracy was a major study in order to reflect the current relationship between the ruler and Islam. This research will look at the role of President Soekarno towards Masyumi in the national political contestation during the Guided Democracy period. The existence of ideological linkages between President Soekarno and President Joko Widodo, makes this research interesting. Are there points of equality between the two as a study of political decision making by a ruler.